2021
DOI: 10.3390/rs13061200
|View full text |Cite
|
Sign up to set email alerts
|

MSDRN: Pansharpening of Multispectral Images via Multi-Scale Deep Residual Network

Abstract: In order to acquire a high resolution multispectral (HRMS) image with the same spectral resolution as multispectral (MS) image and the same spatial resolution as panchromatic (PAN) image, pansharpening, a typical and hot image fusion topic, has been well researched. Various pansharpening methods that are based on convolutional neural networks (CNN) with different architectures have been introduced by prior works. However, different scale information of the source images is not considered by these methods, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…p, q are typically set to 1 and α, β are the tradeoff coefficients, usually α = β = 1 [31]. UQI is the universal image quality indices defined as Equation (15), where σ xy is the covariance of x and y, x, y are the average of x and y, and σ x 2 , σ y 2 are the variance of x and y, respectively. From Equations ( 12)-( 15), it can be concluded that D λ measures the distance of the band correlation between fusion result and MS image.…”
Section: No-reference Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…p, q are typically set to 1 and α, β are the tradeoff coefficients, usually α = β = 1 [31]. UQI is the universal image quality indices defined as Equation (15), where σ xy is the covariance of x and y, x, y are the average of x and y, and σ x 2 , σ y 2 are the variance of x and y, respectively. From Equations ( 12)-( 15), it can be concluded that D λ measures the distance of the band correlation between fusion result and MS image.…”
Section: No-reference Lossmentioning
confidence: 99%
“…Due to the continuous combination of the extracted high-level image features and low-level features, the residual network alleviates the problem of image details loss with the deepening of the CNN. However, by constantly feeding the shallow features into the deep network, the number of network parameters and the quantities of features to be processed for the deep layer of the network will increase, which will make the network more complicated [13][14][15]. Subsequently, some methods [16] are proposed to improve the running efficiency of the residual network in the field of computer vision.…”
Section: Introductionmentioning
confidence: 99%
“…e structure characteristics of several common residual neural networks are shown as follows [16][17][18] 4…”
Section: Basis Of Residual Neural Networkmentioning
confidence: 99%
“…Wang W., et al [7] designed a multi-scale deep residual network (MSDRN) for pan-sharpening the MS images. Here, multi-level network was employed for scaling the source images.…”
Section: Neural Network-based Techniquesmentioning
confidence: 99%